The Relationship of Academic Self-Efficacy to Academic Motivation of Junior High School Students From Families Towards Prosperity - Muhammad Arif Furqon (Jurnal KESANS : Kesehatan dan Sains, 2021)
Every individual behaves based on motives. The existence of a motive makes behavior directed towards the goals to be achieved by someone. Someone who has the motivation, based on the existence of self-confidence called self-efficacy. Especially in an academic setting, students will be motivated if they have confidence in the achievements they will achieve. The purpose of the study was to determine the relationship between academic self-efficacy and academic motivation of junior high school students from Families to Prosperity. The subjects in this study were 134 State Junior High School students in grades VII and VIII from those belonging to families towards prosperity. This research design uses a quantitative approach with regression analysis. The results of this study indicate that academic self-efficacy has an influence of 34% on the academic motivation of KMS students. The results of this study indicate that there is a relationship between self-efficacy and academic motivation of students who come from families to prosper. Self-efficacy as an internal factor has a greater role than external factors in increasing the academic motivation of students with family backgrounds towards prosperity